PENGGUNAAN MEDIA POP UP DAN VIDEO LAWAKAN DALAM MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS X SMAN 3 KUPANG - Napa Maol, Priska Kusuma Wardani; Djawa, Alex; Ga, Adrinika H. (Jurnal Lazuardi, 2024)
Success in conveying the essence of learning material is influenced by learning media. In language learning, interesting media tends to improve language skills. Joke videos can improve students' critical thinking skills in picking messages and criticism from jokes and joke texts packaged in pop ups help students improvise in performing jokes. The aim of this research is to use media to improve students' speaking skills in the material of presenting single jokes with the help of pop up media and joke videos. This research is Classroom Action Research (PTK). Research data is presented descriptively. The research subjects were 36 students in class X B at SMAN 3 Kupang. The data presented in this research are 1) the results of teacher and student performance tests, and the results of student speaking tests. In cycle I, classical completion only achieved 69.44%, then it increased in cycle II to 100%. Judging from the data from teacher and student observations in cycle I, it was 42.10% and 45.05%, then increased in cycle II to 80.26% and 84.21%. Based on these achievements, it can be concluded that the use of pop up media and learning videos can improve speaking skills in single joke text material for class X B students at SMAN 3 Kupang.